1987
DOI: 10.3109/00048678709160928
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from the Insulin Story in Psychiatry

Abstract: For nearly 20 years, from the mid-1930s until the mid-1950s, early cases of schizophrenia were treated, and surprisingly successfully treated, by deep insulin coma therapy. This paper is an attempt to explore what, if any, lessons there are to be gained for us 30 years later from a treatment regime that turned out to have nothing to do with insulin per se. Such lessons as there may be from our recent historical past may help us to foster our critical acumen and commonsense as we try in our daily practice to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…After the discovery of an effective neuroleptic, investigators became bold enough to conduct adequately controlled studies on insulin coma. By excluding all confounders, they demonstrated that the crucial ingredients were the vastly greater care the insulin coma patients received and the better morale of their doctors and nurses (Cramand, 1987) rather than the "religious" adherence to insulin induced coma per se (Ackner, Harris & Oldham, 1957). We suspect that the world literature reviewed by Koenig et al (2001) is correct in uniformly asserting that greater religious involvement reduces depressive symptomatology.…”
Section: Discussionmentioning
confidence: 98%
“…After the discovery of an effective neuroleptic, investigators became bold enough to conduct adequately controlled studies on insulin coma. By excluding all confounders, they demonstrated that the crucial ingredients were the vastly greater care the insulin coma patients received and the better morale of their doctors and nurses (Cramand, 1987) rather than the "religious" adherence to insulin induced coma per se (Ackner, Harris & Oldham, 1957). We suspect that the world literature reviewed by Koenig et al (2001) is correct in uniformly asserting that greater religious involvement reduces depressive symptomatology.…”
Section: Discussionmentioning
confidence: 98%
“…Between 1930s and 1950s (when neuroleptics were introduced), insulin coma therapy was a treatment of choice for schizophrenia [Cramond, 1987]. While it fell into disfavor for several reasons, its effectiveness in some patients has never been understood fully.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that authorities pronounced favourably on this treatment may also have led those involved with the care of patients to take risks they might not otherwise have taken -leading to an Oedipus effect, whereby oracular pronouncements act to bring about the state they pronounce on (Shepherd, 1990). In due course, when enthusiasm fades and the oracle stops pronouncing, the rate of response to the treatment in question falls -this is certainly what happened with insulin (Cramond, 1987).…”
Section: Aozapine and Negative Symptomsmentioning
confidence: 98%
“…Indeed, a consideration of such issues might prompt a comparison between dozapine and insulin. The evidence that insulin was more effective than other treatments for schizophrenia at the time of its introduction was never compelling (Cramond, 1987;Shepherd, 1990). Yet the treatment was introduced widely; it appears that few self-respecting treatment facilities needed much persuasion on the question of setting aside considerable funds to establish insulin units (Cramond, 1987).…”
Section: Aozapine and Negative Symptomsmentioning
confidence: 99%
See 1 more Smart Citation